Oxidative stress and inflammation, two features associated with a high percentage body fat, and that may lead to diabetes mellitus and metabolic syndrome. (18th December 2018) - Darroudi, Susan; Fereydouni, Narges; Tayefi, Maryam; Ahmadnezhad, Mahsa; Zamani, Parvin; Tayefi, Batool; Kharazmi, Jasmin; Tavalaie, Shima; Heidari‐Bakavoli, Alireza; Azarpajouh, Mahmoud R.; Ferns, Gordon A.; Mohammadpour, Amir H.; et al.
Abstract: Obesity is an important feature of the metabolic syndrome and is associated with an increased risk of type 2 diabetes mellitus, cardiovascular disease, and some cancers. The aim of this study was to determine the relationship between body fat percentage and an imbalance of the prooxidant/antioxidant balance (PAB), serum superoxide dismutase (SOD1) and inflammation (serum hs‐CRP) and increase risk of metabolic syndrome and diabetes mellitus. In this study, 9154 individuals were recruited as part of the Mashhad Stroke and Heart Association Disorder (MASHAD) study. Subjects were categorized into two groups according to body fat percentage as defined >25% in male and > 30% in female, according to gender. Biochemical factors, including serum PAB, SOD1, and hs‐CRP were measured in all subjects. SPSS version 18 was used for statistical analyses for all. GraphPad Prism 6 for figures was used. Of total number of subjects (9154), 6748 (73.7%) were found to have a high body fat (BF) percentage. Serum hs‐CRP and PAB were significantly higher in individuals with a high BF percentage ( P < 0.05) but SOD1 was not significantly different between the two groups ( P > 0.05). BF percentage, serum PAB and serum hs‐CRP were significantly higher in individuals with metabolic syndrome and diabetes versus those without metabolic syndrome and diabetes mellitus ( P < 0.05), however serum SOD1 was significantly lower in individuals with metabolic syndrome ( P < 0.005). Oxidative stress and inflammation are two factors that may link the presence of high BF percentage with the development of metabolic syndrome, diabetes, and cardiovascular disease. © 2018 BioFactors, 45(1):35–42, 2019